Inter-pulse Interval Affects the Size of Single-pulse TMS-induced Motor Evoked Potentials: A Reliability Study - Vaseghi, Bita (Basic Clin Neurosci, 2015)
INTRODUCTION: Measuring the size of motor evoked potentials (MEPs) induced by transcranial magnetic stimulation (TMS) is an investigational technique to show the level of corticospinal excitability; however, some of the fundamental methodological aspects of TMS (such as the effects of inter-pulse intervals (IPI) on MEP size) are not fully understood, this issue raises concerns about the reliability of MEPs, especially in pre-test post-test studies. METHODS: MEP size at short and long IPIs was assessed during two separate sessions. Inter- and intra-session reliability of MEP size also was assessed at both short and long IPIs. RESULTS: The results indicated that long IPIs induced larger MEPs (P< 0.05) across all time points. The intra-class correlation coefficient (ICC) indicated high intra- and inter-session reliability for short (0.87 to 0.96) and long (0.80 to 0.97) IPIs respectively. The amplitude of MEPs also had high intersession reliability for short (ICC=0.87) and long (ICC = 0.80) IPIs. DISCUSSION: This study provides evidence that the length of IPIs determines the size of MEPs. As a result, it is recommended to add the length of IPI to the international checklist of considerations for TMS application.